Experiences of family caregivers of patients with post-traumatic hydrocephalus from hospital to home: a qualitative study - Jia-nan Wang; La-mei Liu; Ronnell Dela Rosa; Meng-jie Sun; Yu-meng Qian; Meng-yao Zhuan Sun; Tong-yao Xu (BMC, 2022)
Abstract Background Post-traumatic hydrocephalus (PTH) is a complication of traumatic brain injury (TBI) that requires treatment and postoperative care. The shunt is one of the main treatments for PTH, which presents with dysfunction and infection. Considering brain injury, hydrocephalus shunt malfunction, and infection, family caregivers need to be responsible for caring for PTH patients, recognizing shunt malfunction and infection, and managing those patients accordingly from hospital to home. Understanding the experiences and needs of caregivers is beneficial for knowing their competency and quality of health care, ameliorating and ensuring future transition care. The study aimed to explore the feelings, experiences, and needs of family caregivers when caring for patients with TBI, PTH and shunts. Methods This was exploratory research of a purposive sample of 12 family caregivers of adult patients with TBI, PTH and shunts in five neurosurgery departments at a general hospital in Zhengzhou, Henan Province, China, using a semi-structured interview method. Data were collected from October 2021 to March 2022 before being analyzed by content analysis methods. Results Caregivers required professional and social knowledge and support in the areas of TBI, PTH and shunts, caregiving interventions, psychological care needs, and health insurance, just as caregivers do, but unlike other general caregivers, care for patients with TBI, PTH, and shunt is fraught with uncertainty and the need to manage shunt setting, and caregivers often experience 'complex emotional reaction' during the transitional period, where care needs and complex emotions may lead to a lack of caregiver confidence, which in turn may affect caregiving behaviors, and experiences that affect care may be mediated through caregiving confidence. The perceived availability of resources, particularly those that are still available to them when they return home, has a significant impact on participants' emotional response and sense of confidence. Conclusions The emotional response and the impact of stressor caregivers after TBI, PTH, and shunt was important, and sometimes confidence in care appeared to be an intermediate and useful factor that needed to be considered as health professionals prepared to develop care resources on how to manage and empower patients with TBI, PTH, and shunt. Meanwhile, there may be gaps and inequities in supportive care for patients diagnosed with TBI, PTH, and shunt in China.